Highly efficient CoOx/SBA-15 catalysts prepared by atomic layer deposition for the epoxidation reaction of styrene. Issue 10 (20th April 2017) - Li, Yunqin; Zhao, Shichao; Hu, Qingmin; Gao, Zhe; Liu, Yequn; Zhang, Jiankang; Qin, Yong
Abstract : CoO x was deposited in SBA-15 by ALD as efficient catalyst for styrene epoxidation, and an ultrathin TiO2 layer was coated firstly to improve performance further. Abstract : Co-based catalysts have been widely studied for the epoxidation reaction of styrene. Herein, we directly introduced CoO x species into SBA-15 by atomic layer deposition (ALD). The CoO x /SBA-15 catalysts exhibit remarkably higher activity and selectivity in epoxidation of styrene than the catalyst prepared by incipient wetness impregnation. This is due to the fact that CoO x nanoclusters were produced by ALD and uniformly dispersed in SBA-15. Furthermore, before the CoO x ALD process, an ultrathin TiO2 layer was coated onto SBA-15 firstly by ALD to modify the active species–support interaction precisely. The obtained catalysts show improved selectivity and stability compared to the unmodified catalysts. This is due to the appropriate interaction between the CoO x and support.